SENGKETA ASURANSI DALAM PEMBIAYAAN MUSYARAKAH: Analisis Putusan No. 967/Pdt.G/2012/PA/Mdn - Bariroh, Muflihatul (Ahkam: Jurnal Hukum Islam, 2017)
The dispute of economic shariah number: 967 / pdt.g / 2012 / pa.mdn registered to the Religion Court of Medan in 2012 has resolved the dispute insurance in musyarakah funding involving two parties, a Sharia bank in Medan as a defendant and its customer as a plaintiff. In this case the judge decided that the plaintiff as the heirs was released from the burden of debt financing the musyarakah with the defendant .This article aims to analyze the conformity of judicial consideration decisions issued by the Religion Court of Medan which is considered against the procedure and the regulations related to the case. This library research uses descriptive analysis, and normative juridical. The data used in this research was secondary data that is inventory file of judicial decisions from Religion Court of Medan number: 967 / pdt.g / 2012 / pa.mdn. The data in this research are composed of the primary material law in the form of legislation, the secondary material law in the form of the law books, magazine, the internet source, journal articles, and verdict analysis written by judges previously.Keywords: Sengketa Asuransi, Pembiayaan Musyarakah